2020
DOI: 10.1371/journal.pone.0236094
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of shock index to pulse oxygen saturation predicting mortality of emergency trauma patients

Abstract: Objective To test the following hypothesis: the ratio of shock index to pulse oxygen saturation can better predict the mortality of emergency trauma patients than shock index. Methods 1723 Patients of trauma admitted to the Emergency Department of the First Affiliated Hospital of Soochow University from 1 November 2016 to 30 November 2019 were retrospectively evaluated. We defined SS as the ratio of SI to SPO2, and the mortality of trauma patients in the emergency department as end-point of outcome. We calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…In this study, SpO2 values and the presence of oxygen administration were added to the characteristics with reference to the NEWS. The literature on the relationship between SpO2 and the prognosis of trauma patients is limited, and the results have been inconsistent 17 . Some studies have reported that SpO2 values are not a predictor of mortality in trauma patients upon arrival at the hospital 18 , while others have reported that they are 1920 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SpO2 values and the presence of oxygen administration were added to the characteristics with reference to the NEWS. The literature on the relationship between SpO2 and the prognosis of trauma patients is limited, and the results have been inconsistent 17 . Some studies have reported that SpO2 values are not a predictor of mortality in trauma patients upon arrival at the hospital 18 , while others have reported that they are 1920 .…”
Section: Discussionmentioning
confidence: 99%
“…To assess the performance of oxygen perfusion without laboratory facilities, the only parameter that can be used clinically is oxygen saturation (SpO 2 ). Oxygen saturation in critically ill patients may reflect microcirculatory conditions, which will also be associated with laboratory markers such as lactate and acid-base deficiency [ 32 ]. Imanieh et al are also in line with this study, integrating oxygen saturation as one of the scoring categories [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Du et al examined COVID-19 patients based on clinical and laboratory criteria and revealed some severe complaints and comorbidities. The five most common complaints in COVID-19 patients were fever (98.9%), dry cough (81.6%), dyspnea (49.7%), fatigue (39.1%), and productive cough (30.7%) [ 32 ]. On the other hand, headaches, fatigue, and productive coughs were more common in the survivor group.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, respiratory adjusted shock index (RASI) and shock index to SpO 2 ratio (SS) have been validated in acute respiratory distress syndrome (ARDS) and community-acquired pneumonia patients to predict the need for mechanical ventilation and hospitalization. 13,14 Jiang and colleagues have successfully applied RASI in sepsis for identifying occult shock and subsequent triage of the patients for the level of care required. 13 Adjusting the cutoff appropriate for age, Ray and colleagues 15 highlighted a better predictive efficacy of on admission SI pediatric age-adjusted (SIPA) over the conventional hemodynamic parameters (SBP, HR) and positive correlation with arterial lactate level.…”
Section: Encouraging Literatures Diverse Patient Populationsmentioning
confidence: 99%